Metaphors about language learning held by young Malaysian learners of English / Surinderjeet Kaur Sarban Singh - Surinderjeet Kaur, Sarban Singh (2019)
This study aims to explore metaphors and their entailments generated by Year 6 (12 year old) pupils from Sekolah Kebangsaan Bangsar, Kuala Lumpur, that describe the process of learning the English language. To elicit these participants’ metaphors, the students were requested to fill in the gaps in the sentence “Learning English is like...because...” The metaphors and the entailments were classified using the thematic analysis. Furthermore, the entailments were analysed to determine whether they aligned with Martinez et el.’s (2001) influential theoretical framework. It was found that the metaphors aligned with the framework. Also, the metaphors were analysed to find out the attitude embedded in them. It was found that both the Higher Proficiency Group and Lower Proficiency Group showed positive attitude towards learning English through metaphors. Knowing the metaphors in learning English could enhance pedagogical practice.